SOSIALISASI MPASI YANG TEPAT SEBAGAI UPAYA PENCEGAHAN STUNTING - Laode Burhanuddin Mursali; Khairunnas Khairunnas; Rizky Anggara; Nala Oktawianda; Asyura Pebriola; Syahkia Vermahdani; Tito Castro Siagian; Khofifa Azhari; Siti Nurhaliza; Abigael Ruthmawati; Imroatul Fadhilah (Bajang Institute, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutrition in the long term, resulting in disrupted growth in children, especially in the first 1000 days of a child's life (HPK). Stunting can occur due to various factors, one of which is a lack of nutritional intake, this can occur when the baby is still in the womb because the mother does not meet her nutritional needs during pregnancy. In addition, another factor that can affect stunting is the provision of inappropriate complementary foods to children under two years old. ). Stunting cases in Sungai Liti village reached 23.9%, this figure is considered high. One of the efforts to overcome and prevent stunting is by increasing the capacity and increasing the number of caregivers for toddlers regarding the pattern of providing them with nutritious MPASI. The method that can be used to increase capacity and knowledge related to MPASI is through outreach. this aims to increase the knowledge of foster mothers so they are able to regulate MPASI patterns and know the nutrition in the MPASI menu and it is hoped that they will be able to prevent and reduce stunting rates in Sungai Liti village. This activity was attended by 43 foster mothers, village midwives and PKK administrators in Sungai Liti village. This socialization material discusses the meaning of stunting, factors that influence stunting, symptoms of stunting, efforts to prevent stunting through complementary foods, and finally innovations for complementary foods made from local and nutritious ingredients according to the age of the toddler. All participants took part in this event with enthusiasm, this was proven by the many participants who asked questions and shared about the material presented, it can be concluded that all participants had knowledge after participating in this socialization activity.